Penerapan Modifikasi Circular Flounce pada Busana Pesta dengan Inspirasi Bunga Calla Lily - Bella Stevania Diwanti; Yulistiana Yulistiana (Universitas Negeri Surabaya, 2023)
The addition of Manipulating fabric to clothing aims to make clothing look more attractive and can be a selling point for the clothing, the application of Circular flounce is one way to create a luxurious impression on dresses. The purpose of this study was to 1) find out the process of making modified circular flounce patterns, 2) find out how to apply circular flounce modifications to evening party dresses inspired by Calla lilies, and 3) find out the result of the evening party dress with the inspiration of the Calla lily flower. The method used is the Double Diamond Design Process, which consists of 4 stages, namely the discover Define, develop, and the last stage deliver. The data collection instrument was conducted by distributing questionnaires on the process, application, and finished results of making party dresses to experts in the field of fashion with a scale of 1 to 4. Data analysis techniques used average descriptive analysis techniques. The results of the research show that 1) to make a party dress, it is necessary to determine the modification pattern of Circular flounce according to the right design and size so that the fall of the flounce wave can be perfect. 2) The finished result is the application of circular flounce modifications to party dresses inspired by calla lilies. 3) The finished results of party dresses inspired by calla lilies get a mean of 3.50 for each indicator, with a very good or appropriate category.